H2S detection using low-cost SnO2 nano-particle Bi-layer OFETs - Surya, Sandeep G.; Ashwath, B. S. Narayan; Mishra, Sushma; Karthik, A. R. B.; Sastry, A. B.; Bhagavatula L. V. Prasad; Rangappa, Dinesh; Rao, V. Ramgopal (Sensors and Actuators B-Chemical, 2016)
In this article, a unique platform with an organic field-effect transistor (OFET) integrated with metal oxide nanoparticles for sensing of H2S gas is presented. Metal oxide nanoparticles such as SnO2 and ZnO synthesized using herbal techniques were used in the fabrication of OFETs using a bi-layer technique. The as -synthesized nanoparticles were characterized by Field Effect Scanning Electron Microscopy (FESEM), X-ray diffraction (XRD) and UV-vis Spectroscopy (UV-vis) to establish the material properties. We showed that the SnO2 based OFETs displayed better response for H2S at room temperature (25 degrees C) compared to the OFETs fabricated with ZnO. The characterization of the sensors by using extracted electrical parameters like field-effect mobility ([1), On -Current (Ion), threshold voltage (VT) and saturation current (ID]) establish the fact that the SnO2 based OFETs detect H2S gas at room temperature. Plausible mechanisms explaining the H2S gas detection by bi-layer film were discussed. On the other hand, the sensitivity of these OFETs against other reducing gases was less. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: bi-layer; H2S detection; Metal-oxide; OFETs; Sensor